Applying traceability in a mine-to-mill context by using particle texture analysis - Oghazi, Pejman; Lund, Cecilia; Pålsson, Bertil; Martinsson, Olof (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2010)
It is possible to have traceability in the mining industry, by parameters and signatures like particle mineralogy, mineral association, texture and mineral liberation. The study is on an apatite-iron ore deposit at Malmberget, Sweden, and characterises an ore body both mineralogically and texturally in a quantitative manner by using analytical methods like optical microscopy, microprobe (EMPA) and an automatic SEM based system, Particle Texture Analysis (PTA). The mineralogy was evaluated by PTA and characterized by modal mineralogy, mineral liberation and mineral associations. Magnetite has a simple outline and straight grain boundaries and the gangue minerals have a finer particle size with a more complicated texture. The PTA analysis also shows that apatite is associated to magnetite as mixed particles, while smaller grains of magnetite are inclusions in feldspar. Result from particle texture analysis shows that there is a connection which link to the mine-to-mill context, and it may be used to create traceability. This link is not the associations of the main ore mineral magnetite, nor the modal mineralogy. Instead, it is the mineral associations of contaminating minerals (apatite and feldspar) that appear to be most promising since they survive from mine to mill. The modal mineralogy may be used to understand how contaminating minerals break into or out of particle size fraction during grinding. Godkänd; 2010; 20100329 (pjmogh)